اقتصاد المعرفة ودوره في تفعیل مؤشرات التنمیة البشریة في الجزائر - نشاد حكیم (Finance and Business Economies Review, 2018)
In this era, we have witnessed a new phase whose most prominent feature is the widespread and unrecognized use of the information revolution and the subsequent knowledge revolution that affected all sectors. Until recent decades, technology, knowledge and intangible materials were not the main determinants of growth. , But this has differed significantly in recent years as the interest in the vast and accelerating interest in intangible resources of knowledge, as one of the most important attempts to achieve the desired development and increase their income and the advancement of their economies. This paper is trying, we have tried to highlight the great role played by the knowledge economy as a modern economic model in activating human development indicators in Algeria (health, education and income).